Pengembangan Wondershare Quiz Creator Sebagai Alat Evaluasi Pada Pembelajaran Sejarah (Pada Siswa SMA Kelas XI IPS 2 di SMA Negeri 1 Sobang) - Nur Silawati, Reni; Rustamana, Agus; Nurhasanah, Ana (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2024)
Abstract Learning evaluation is a very important task, with the teacher's creativity in using effective and efficient and fun evaluation tools, it’s hoped that it will be more easily accepted by students and make it easier for teachers to provide learning evaluations. The method used in this study is the research and development method or Research and Development which refers to the ADDIE development model which consists of five stages which include analysis, design, development, implementation and evaluation. evaluation). The advantage of using Wondershare Quiz Creator is that it makes it easier for teachers to prepare and compile learning evaluation tools. The results of this study indicate that the Wondershare Quiz Creator evaluation tool which has been validated by material experts obtains a percentage score of 94.2% with very valid criteria, validation by media design experts after revision obtains a percentage score of 93% with very valid criteria, and student responses obtain a score percentage of 86.1% with very valid criteria. The Wondershare Quiz Creator application is said to have an effect on history learning seen from the development success rate which obtained a percentage score of 85.7%. The developed Wondershare Quiz Creator is suitable for use as an evaluation tool on the material of Indonesian Maritime Kingdoms during the Islamic Period for students of class XI IPS 2 at SMA Negeri 1 Sobang. Key Words: Wondershare Quiz Creator, ADDIE, Evaluation, History Learning